Estudo retrospectivo de dermatopatias em animais domésticos - Amado, Giuliano Palha (2017)
As a result of the advancement of veterinary dermatology specialization, more accurate and earlier diagnosis have been acquired. Tutors have easier access to information and look for quick solutions for their animals. The histopathological test is a great ally to the veterinarian in the diagnosis of dermatopathies, since in some cases it is the only one to clarify alterations of the altered tissue. In the chapter 1 the study aimed to collect retrospective data on dermatopathies in dogs and cats treated at a veterinary clinic specialized in dermatology, in the city of João Pessoa - Paraíba. In the chapter 2 another goal was to investigate the causes of photosensitization and allergic dermatitis in a cattle from Brazilian Northeast, through a retrospective study.All the animals have gone through detailed data collection in their records and anamnesis.In dogs and cats, histopathological examination was only requested in cases that it was not possible to diagnose dermatopathy by cytology, acetate tape test, trichrome and fungal culture, or when its indication was the best option. In the 30 dogs studied, there were predominant neoplasias (19 - 59.38%), followed by inflammatory (7 - 21.88%), autoimmune (3 - 9,38%) and infectious diseases (2-6.25%) as well as follicularmucinose (1 - 3.13%).In the felines, the dermatopathies were divided into neoplastic (5 cases - 55.55%), allergic (2 cases - 22.22%), inflammatory (1 case - 11.11%) and fungal infectious skin diseases (1 case – 11.11%). Regarding the dogs, the tumor with the greatest participation was the mastocytoma. As for the felines, the squamous cell carcinoma.In the second chapter of this dissertation, diagnoses in ruminants and equidae filed at the Laboratory of Veterinary Pathology Federal University of Paraíba were reviewed. Only animals with cutaneous manifestations were included in the study. These were divided according to sex and age. In regard tothe epidemiology, the time of the year of the disease occurrence and the environmental factors involved were defined, as well as the total prevalence of dermatitis associated with photosensitization and allergic hypersensitivity.Cases of primary photosensitization were diagnosed in goats, cattle, asinines, horses and sheep, all associated with the intake of the Froelichiahumboldtiana plant, and they were more severe in the asininos. Brachiariadecumbens, Enterolobiumcontortisiliquum and Lantana chamber were the plants involved in the cases of secondary photosensitization. The cases of allergic dermatitis were restricted to five sheep and one equine and were caused by the bite of culicoid insects (Culexspp). There was no relation with seasonality. Moreover, the main complaints of the breeders of all animals involved in the cases were pruritus and discomfort. Histopathology has shown to be an accurate diagnostic tool for the diagnosis of skin diseases of companion animals and animals of production. Neoplasias are the major diseases of dogs and cats in the studied area. Photosensitization causes serious problems for the Brazilian northeastern herds and it is mainly caused by Froelichiahumboldtiana, attacking both ruminants and equidae.